Using linear discriminant analysis method based on genetic algorithms to solve the classifying problem in medical field. - Phúc, Nguyễn Công; Liên, Doãn Hồ; Viên, Cao Văn; Thủy, Cù Thu (Journal of Computer Science and Cybernetics, 2012)
-